PENERAPAN MODEL PROBLEM BASED LEARNING DISERTAI LKPD PADA MATERI PROGRAM LINEAR DI SMA - Pardede, Tanti Eviliana; Hartoyo, Agung; B.S, Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effectiveness of the application of the Problem Based Learning model accompanied by LKPD on the Linear Program material in the Taruna Bumi Khatulistiwa High School. The type of experimental design used in this study were pre-experimental design using one-shot case study as the form of the design. The aspect used to determine the effectiveness of learning using a cooperative model of probing-prompting type are the teacherâ€™s teaching and learning management, student activities, responses, and learning outcomes. Data collection techniques used were measurement, observation, and indirect communication techniques. The data collection tool used was the teacher's observation observation sheet in managing learning, observation sheets of student activities, student response to the questionnaires, and student learning assessment results. The data were analyzed descriptively. The results obtained were the implementation of the teacher in managing learning is very good, the activities of students are classified as very active, the response of students is very positive and the completeness of student learning outcomes in a classical manner has been achieved. Because all effectiveness criteria are met, learning using the Problem Based Learning model accompanied by LKPD on linear program material in the Taruna Bumi Khatulistiwa High School is said to be effective.Â Keywords: Learning application, Problem Based Learning Model accompanied by LKPD, Linear Program Material.